2018
DOI: 10.1093/geroni/igy027
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications Sought From Mobile Phones and Loneliness Among Japanese Midlife and Older Adults: A Mediation Analysis

Abstract: Background and ObjectivesMobile phone use is increasing among older adults, yet few studies have examined how the various purposes for which mobile phones are used affect loneliness and through what mechanisms. This study aims to address the gap by examining if different uses and gratifications of mobile phone are associated with loneliness and whether there is a mediation effect through face-to-face social interaction.Research Design and MethodsParticipants included 1,318 mobile phone users drawn from a natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
0
21
1
Order By: Relevance
“…In Singapore, even among older adults deemed to be at low risk of social isolation, 44.7% were sometimes lonely or mostly lonely [ 39 ], highlighting the different social needs of these 2 groups. At present, evidence supporting the effectiveness of social media in reducing loneliness remains mixed [ 47 , 48 ]. Furthermore, the greater visibility into the lives of their contacts afforded by the increased access on social media may abet upward social comparison and intensify feelings of loneliness [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, even among older adults deemed to be at low risk of social isolation, 44.7% were sometimes lonely or mostly lonely [ 39 ], highlighting the different social needs of these 2 groups. At present, evidence supporting the effectiveness of social media in reducing loneliness remains mixed [ 47 , 48 ]. Furthermore, the greater visibility into the lives of their contacts afforded by the increased access on social media may abet upward social comparison and intensify feelings of loneliness [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey was originally designed to examine older consumers’ behavior and attitudes toward new technology in Japan and was conducted by a well-established Tokyo-based market and public-opinion survey firm (Cheron & Kohlbacher, 2018; Wang et al, 2018). The survey was nationwide by accessing the Japanese household registration data through local administrations.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, a previous study identified ten components dealing with the U&G theory in the use of the social media: social interaction, information seeking, pass time, entertainment, relaxation, communicatory utility, convenience utility, expression of opinion, information sharing, and surveillance/knowledge about others (Whiting & Williams, 2013). Another identical finding showed that social media may create socialite, entertain oneself, and spare time (Wang et al, 2018). The previous studies described something in general, where some concepts could be united into a representative concept such as consumption, production and information dissemination.…”
Section: Motivation and Gratificationmentioning
confidence: 99%
“…The composition of these components socially leads to losses and benefits. This means there are benefits to be gained and even one will be lost as satisfaction (Muhammad, 2018;Opeyemi, Shariff, Abas, & Periyayya, 2018;Wang, Matz-Costa, Miller, Carr, & Kohlbacher, 2018;Xu & Takai, 2018), if he doesn't join or is not in a social media group. The third is social networking.…”
Section: Motivation and Gratificationmentioning
confidence: 99%